Systematic position of the Afrotropical species described in Trachyphloeini (Coleoptera: Curculionidae: Entiminae) - Borovec, Roman; Skuhrovec, Jiří (Zootaxa, 2017)
The Afrotropical species described as Trachyphloeini Lacordaire, 1863 were examined and their taxonomic status is revised. Atrachyphloeus Voss, 1962 is proposed as a junior synonym of Phaylomerinthus Schoenherr, 1842, Cathormiocerus africanus Hoffmann, 1965 as a junior synonym of Tapinomorphus sylvicola Voss, 1962 and Trachyphloeus pustulifer Voss, 1959 as a junior synonym of Platycopes tuberculatus Marshall, 1906. Atrachyphloeus convergens Voss, 1962 is transferred to the genus Phaylomerinthus Schoenherr, 1842, Trachyphloeus hardenbergi Marshall, 1923 and T. notulatus Boheman, 1842 to Glyptosomus Schoenherr, 1847, Trachyphloeus nanus Fåhraeus, 1871 to Pentatrachyphloeus Voss, 1974, Trachyphloeus pustulifer Voss, 1959 to Platycopes Schoenherr, 1823 and Trachyphloeus setiger Fåhraeus, 1871 to Phaylomerinthus Schoenherr, 1842. “Trachyphloeosoma” brevicolle Voss, 1974, “Trachyphloeus” brevis Boheman, 1842, “T”. nodifrons Hoffmann, 1968 and “T”. squalidus Boheman, 1842 are provisionally left in their current genera, but new genera for them will be described in future papers. The genus Phaylomerinthus Schoenherr, 1842 has been redefined and redescribed. Lectotypes for the following species are designated (current names added in brackets where different): Cathormiocerus africanus Hoffmann, 1965 (Tapinomorphus sylvicola Voss, 1962), Trachyphloeus hardenbergi Marshall, 1923 (Glyptosomus hardenbergi (Marshall, 1923)), Trachyphloeus nanus Fåhraeus, 1871 (Pentatrachyphloeus nanus (Fåhraeus, 1871)), Trachyphloeus notulatus Boheman, 1842 (Glyptosomus notulatus (Boheman, 1842)), Trachyphloeus pustulifer Voss, 1959 (Platycopes tuberculatus (Marshall, 1906)), Trachyphloeus setiger Fåhraeus, 1871 (Phaylomerinthus setiger (Fåhraeus, 1871)), “Trachyphloeus” brevis Boheman in Schoenherr, 1842 and “Trachyphloeus” squalidus Boheman in Schoenherr, 1842. Two paralectotypes of Cathormiocerus africanus Hoffmann, 1965 from Tanzania are described as a new species, Tapinomorphus franzi sp. n. All type specimens are illustrated.